The Influence of Perceived Usefulness, Perceived Ease Of Use and Social Influence on Mobile Commerce Usage Activities - M. Rizky Mahaputra; M. Ridho Mahaputra (Greenation Research & Yayasan Global Resarch National, 2023)
This research aims to analyze the influence of perceived usefulness, perceived ease of use and social influence on mobile commerce usage activities in Padang State University's students. The type of research is causative. The numbers of the sample were 100 respondents who had been taken by accidental sampling technique. The data analysis technique used Structural Equation Modeling (SEM) with the 3.0 WarpPLS program. The results of this research show that: (1) Perceived usefulness has a positive and significant influence on the mobile commerce usage activities in Padang State University students. (2) Perceived ease of use has positive and not significant influence on mobile commerce usage activities in Padang State University's students. (3) Social influence positive and significant influence on mobile commerce usage activities in Padang State University's students.